Pediatrician and parental evaluation of child neurodevelopment at 2 years of age - Giulia Segre; Antonio Clavenna; Elisa Roberti; Francesca Scarpellini; Massimo Cartabia; Chiara Pandolfini; Valeria Tessarollo; Ilaria Costantino; Maurizio Bonati (BMC Pediatrics, 2024)
Abstract Background The early identification of infants with a risk for neurodevelopmental disorders in the first few years of life is essential for better developmental outcomes. Screenings should be carried out by combining the family pediatricians’ and parents’ perspectives, the two fundamental sources of information on children’s health. The present study has three aims: (a) to test the feasibility of parent-report instruments to detect warning signs in their children’s development; (b) to ascertain whether there is an agreement between the family pediatricians’ (FP) clinical judgments of warning signs and the parental perceptions; (c) to determine whether there is a link between parents’ distress and child development. Methods Within the NASCITA birth cohort, in addition to the family pediatrician’s clinical evaluation with routine tools, the Modified Checklist for Autism in Toddlers, Revised (M-CHAT-R) was completed by parents to assess the child’s language, social skills, behavior, and sensory areas. Parents were also asked to complete the Parenting Stress Index, Short Form (PSI-SF) to verify the magnitude of stress in the parent-child system. Univariate and multivariate analyses were performed to evaluate the association between child and parental characteristics and the presence of warning signs. Results The follow-up assessment was completed for 435 infants: 69 (15.8%) presented warning signs: 43 in the pediatrician’s assessment and 36 in the M-CHAT-R (10 in both). A total of 16 children (14 with warning signs) received a diagnosis after a specialist evaluation. Being male (OR 2.46, 95%CI: 1.23–4.91) and having sleep disorders (OR 2.43, 95% CI 1.17–5.04) was associated with a greater likelihood of warning signs in the multivariate analysis, while reading aloud was a protective factor (not exposed versus exposed (OR = 3.14; 95% CI 1.60–6.17). For 73 children (18.4%), at least one parent tested positive for PSI-SF. An increased prevalence of parental distress was observed in children with warning signs (OR 2.36, 95% CI 1.27–4.37). Conclusions Integrating physician and parental perspectives during well-child visits and in clinical practice appears feasible and can improve the identification of children at risk of developmental disorders.